Policy resistance to paradigm shifts: Inclusive growth and innovation in Canada. (1st June 2022) - Jansen, Alix J.; Robbins, Mark
Abstract: We assess Canada's labour market policy mix in order to determine whether the inclusive growth and innovation agenda indicates that technological change has triggered a policy paradigm shift. Our analysis of four policy areas concerning labour market access indicates no paradigm shift has occurred. Instead, the agenda is an example of policy resistance: first‐ and second‐order policy changes (changes to policy settings) maintain the status quo of labour market arrangements. The result is a revised set of supply‐side policies unlikely to reorganize the labour market. Technological disruption and the COVID‐19 pandemic offer opportunities to reorganize Canada's labour market policies' current policy mix, but, even under the banner of inclusive innovation, this shift is unlikely to happen. Sommaire: Cet article évalue l'agencement des politiques du marché du travail canadien afin de déterminer si le programme de croissance et d'innovation inclusives indique que le changement technologique a déclenché une modification du paradigme politique. Notre analyse de quatre domaines politiques concernant l'accès au marché du travail démontre qu'aucun changement de paradigme ne s'est produit. Plutôt, le programme est un exemple de résistance politique : les changements de politiques de premier et de second ordre (changements des orientations de politiques) maintiennent le statu quo des dispositions du marché du travail. Il en résulte un ensemble révisé de politiques axées sur l'offre peu susceptible de réorganiser le marché du travail. Les perturbations technologiques et la pandémie de COVID‐19 offrent des possibilités de réorganiser l'agencement actuel des politiques du marché du travail du Canada, cependant, même sous la bannière de l'innovation inclusive, ce changement est peu susceptible de se produire.